RZYMSKA DYSCYPLINA WOJSKOWA W UJĘCIU NICCOLÒ MACHIAVELLEGO - Faszcza, Michał Norbert (Zeszyty Prawnicze, 2016)
Machiavelli on Roman Military Discipline Summary The importance of Niccolò Machiavelli’s work for the evolution of modern political ideas is indisputable, but the organisation of military forces was an equally important issue for him. Although most researchers usually ignore this aspect, Machiavelli’s ideas exerted a significant influence on subsequent developments in European military discipline. He was inspired to a large extent by the works of the ancien authors containing descriptions of terms of service in the Roman legions. His attention focused on the Republican period, though he also examined episodes from the Imperial era. Nowadays he is recognised as one of the most influential authors of military treatises, whose ideas on military discipline had a substantial influence on its evolution.